Solution to strengthen bad debt processing at VAMC = Giải pháp tăng cường xử lý nợ xấu tại VAMC - Vũ, Ngọc Minh (2020)
In the context that Vietnam does not use budget capital, VAMC has been the most effective and feasible tool to handle bad debts, contributing to solving difficulties for enterprises with debt restructuring and exemption. reducing interest rates, even accessing loans of credit institutions. As a newly established institution with many difficulties, the initial results of VAMC have supported to accelerate the handling of bad debts. In the next phase, VAMC needs to focus all its efforts on debt settlement (selling debts, selling assets, etc.) and buying debts at market prices for newly arising bad debts, gradually reducing debt purchase by special bonds. VAMC operates in a centralized debt management model. Finding solutions to strengthen the management of bad debt trading at VAMC is a practical requirement. The study of solutions to improve the model and enhance the handling of bad debts for VAMC has achieved some research objectives as follows: Firstly, systematize the theoretical basis for bad debts, buy and sell bad debts, focus on presenting the contents and factors affecting bad debt trading activities at AMCs. In addition, the study also highlighted AMC's experience in handling bad debts in some countries from the world and from that drawn for AMC in Vietnam. Secondly, analyzing the status of dealing with bad debts at VAMC for the period of 2016-2018, thereby making comments and assessments of the actual management of bad debt trading at VAMC, indicating the achieved and surviving results. and the causes of the problems in trading, handling bad debts at VAMC over the past time. Thirdly, based on the results of the situation analysis, the study proposes solutions to enhance the handling of bad debts at VAMC until 2025. The proposed solutions include: Restructuring the organizational structure, improving efficiency results of VAMC; Human resource development; Upgrading information technology infrastructure; Solutions on capital and financial capacity; Solution to perfect the picture of buying, selling and handling bad debts of VAMC.